Ecological thresholds of toxic plants for sheep production and ecosystem multifunctionality and their trade-off in an alpine meadow. (1st December 2022) - Wang, Yingxin; Sun, Yi; Liu, Yang; Wang, Zhaofeng; Chang, Shenghua; Qian, Yongqiang; Chu, Jianmin; Hou, Fujiang
Abstract: Toxic plants are a natural component of alpine meadow which co-evolved with Tibetan sheep for thousands of years. One challenge for indigenous herders is to know the ecological thresholds of toxic plants and maintain their vital functions in ways that are compatible with economic income and ecological conservation. To achieve this, field trials with Tibetan sheep grazing in alpine meadow were conducted to examine the ecological thresholds of toxic plants for sheep production and ecosystem functions and their trade-offs. Our results demonstrated that the changing point values of biomass proportion of toxic plants for dry matter intake and liveweight gain of sheep were 17% and 22%, respectively. The changing point value of biomass (richness) proportion of toxic plants for soil carbon accumulation index was 31% (59%), for soil nutrient cycling index was 38% (42%), and for ecosystem multifunctionality index was 28% (50%). The trade-off between liveweight gain of sheep and ecosystem multifunctionality first decreased and then increased along the gradient of biomass proportion of toxic plants (the value of changing point was 37%), and had a significant negative correlation with richness of toxic plants. In addition, structural equation modeling indicated that toxic plants can affect the trade-off between liveweight gain of sheep and ecosystem multifunctionality though increasing acid detergent fiber of plant and decreasing plant species richness, belowground biomass and soil total phosphorus. Consequently, opinions towards toxic plants should shift from the conventional view that they are serious threat to grassland ecosystem health to an inclusive understanding that they are beneficial to livestock and ecosystem functions under certain ecological thresholds. Highlights: The thresholds of toxic plants for LWG of sheep and EMF were 22% and 28%. The changing point of toxic plants for trade-off between sheep LWG and EMF was 37%. Toxic plants affect the trade-offs via altering key parameters of plant and soil. We proposed a new comprehensive classification system of toxic plants.